The impact of hypoxia and cannabinoids on the differentiation of adult rat mesenchymal stem cells in bone and cartilage tissue engineering - Kanichai, Manoj (Trinity College (Dublin, Ireland). Department of Physiology, 2009)
Adult mesenchymal stem cells (MSCs) have the potential to self-renew and differentiate into cartilage, bone, muscle and fat. This subset of bone marrow stromal cells therefore holds great potential for tissue engineering purposes. To-date no successful treatment is available for many cartilage ailments such as rheumatoid arthritis and bone disorders such as osteoporosis. The overall purpose of this research project was to identify the factors that stimulate rat MSC differentiation along the chondrogenic and osteogenic lineages in order to improve in vitro tissue engineering strategies. The impact of a low oxygen environment (hypoxia) was investigated in the regulation of MSC chondrogenesis. MSCs maintained in the presence of TGF-P and dexamethasone in a normoxic environment displayed increased collagen II expression and proteoglycan deposition which concluded that rat MSCs undergo chondrogenic differentiation. Exposure of MSCs to chondrogenic factors for 14 days in normoxia, followed by 7 days in hypoxia (2% oxygen) showed a significantly enhanced chondrogenesis, which verified that a reduced oxygen tension supports MSC differentiation along the chondrogenic route, fhe reduced oxygen environment augmented HIP-la nuclear accumulation, in addition, transactivation of HlF-la was in an AKT and p38 MAPK-dependent mode. A role for HIF-la in the chondrogenic differentiation of MSCs was demonstrated by the prevention of hypoxia-mediated induction of chondrogenesis by siRNA-mediated knockdown of HiF-1 a.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin